2008
DOI: 10.1002/eji.200737348
|View full text |Cite
|
Sign up to set email alerts
|

Th17 development and autoimmune arthritis in the absence of reactive oxygen species

Abstract: Dendritic cells (DC) express a functional NADPH oxidase and produce reactive oxygen species (ROS) upon interaction with microbes and T cells. Exposure to ROS leads to DC activation and maturation, as evidenced by phenotypic and functional changes. We have evaluated how endogenous ROS production affects the cytokine secretion pattern and T cell-activating capacity of bone marrow-derived murine DC. DC treated with ROS scavengers, as well as DC from mice that lack a functional NADPH oxidase (and thereby inherentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 48 publications
3
58
0
Order By: Relevance
“…Upon potent immune activation (e.g., efficient antigen presentation by DC), the immune-suppressive effect of Mph may be overwhelmed. This hypothesis is in line with the observation that both patients with CGD and mice with a nonfunctional Nox2 are more prone to develop autoimmunity (8,10,44,29,45). This observation suggests that Mphderived ROS may protect against (auto-)immune activation.…”
Section: Mm) After 5 D These T Cells Were Used As Suppressor Cells supporting
confidence: 86%
“…Upon potent immune activation (e.g., efficient antigen presentation by DC), the immune-suppressive effect of Mph may be overwhelmed. This hypothesis is in line with the observation that both patients with CGD and mice with a nonfunctional Nox2 are more prone to develop autoimmunity (8,10,44,29,45). This observation suggests that Mphderived ROS may protect against (auto-)immune activation.…”
Section: Mm) After 5 D These T Cells Were Used As Suppressor Cells supporting
confidence: 86%
“…Interestingly, mice lacking p47 phox or gp91 phox were lethally susceptible to microbial infection, developed granulomatous inflammation similar to symptoms in human CGD patients (9,10), and demonstrated intensified chondrocyte destruction and joint inflammation in an experimental arthritis model (11)(12)(13). Inactivation of p22 phox also resulted in clinically CGD-like immune defects in mice due to the inability of phagocytes to produce bacteria-killing ROS (14).…”
mentioning
confidence: 98%
“…Imbalance between Th1/Th17 and Treg cells is closely associated with autoimmune disease. Previous studies of NOX2-deficient mice have reported increased arthritis development and enhanced Th17 and IFN-γ production, but only upon stimulation with chicken type 2 collagen (CII) and complete Freund's adjuvant (CFA), and found evidence that NOX2-deficient dendritic cells produced higher levels of TGF-β and IL-6 than WT cells, thus resulting in enhanced TH17 development in NOX2 KO mice (11,13). However, the effects of NOX2 deficiency on intrinsic IL-17 production between WT and KO T cells have not yet been determined.…”
mentioning
confidence: 99%
“…Although traditionally reactive oxygen species are linked with the progression of inflammatory diseases, it is currently known that elevated ROS levels in tissues due to hyperbaric oxygen therapy with simultaneous presence of immunomodulating molecules indoleamine-2,3-dioxygenase (IDO) and hypoxiainducible factor 1α (HIF-1α), has a key effect on the function and differentiation of T regulatory cells (Tregs) [54,55,56,57].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…These cells -depending on current ROS tissue status and expression of one of the regulatory moleculesmay differentiate in two directions: FoxP3 + Tregs (in the case of IDO expression) or TH17 (in the case of HIF-1α expression), where an advantage of differentiation in one direction results in the simultaneous inhibition of differentiation in the opposite direction [14,54,55,58,59]. These are important observations, considering the studies conducted by Faleo et al, who found that FoxP3 + Tregs may be involved in the mechanism of preventive effect of HBOT in an animal model (NOD mice) of autoimmune diabetes [21].…”
Section: Research Results and Discussionmentioning
confidence: 99%